Dynamic Simulation and Analysis of Large-Scale Debris Flow Field. (9th May 2022) - Ma, Zongyuan; Liu, Jianqiang
Abstract : The method of two-phase flow is used to analyze the three-dimensional debris flow field via the theory of computational fluid dynamics (CFD). The theory of computational fluid dynamics and finite volume method is introduced briefly, and the rheological characteristic of non-Newtonian fluid is illuminated. The three-dimensional topography model of Niwan gully was established, and the three-dimensional debris flow field was analyzed. The values and distributions of velocity and pressure field of the debris flow have been obtained; the relationship between the shear strain rate, viscosity, and velocity was analyzed. The results suggest that it is more accurate to catch the free surface of debris flow using the method of two-phase flow. The sediment area of the Niwan gully debris flow can be estimated quickly, and it may have significance for the engineering prevention of debris flow disasters.